A global dataset of synthetic tropical cyclone tracks for the El Niño‒Southern Oscillation - Itxaso Odériz; Iñigo J. Losada (Scientific Data)
Abstract Tropical cyclones have devastating consequences, ranging from economic damage to health impacts with impacts varying annually. El Niño‒Southern Oscillation (ENSO) is the primary climate mode that influences interannual timescales, with significant implications for tropical cyclone activity across different basins. An extensive dataset is essential for the accurate assessment of the interannual variability in tropical cyclone risk related to this climate mode. Herein, we present a global dataset of 12,000 years of synthetic storm tracks, representing each ENSO phase (El Niño, La Niña, and neutral phases) over the entire period from 1980 to 2021. This dataset was validated by comparison with observations from IBTrACS, providing a valuable dataset for including interannual variability in tropical cyclone risk assessment, attribution, and detection studies. It also serves as a benchmark for the scientific community.